2015
DOI: 10.1371/journal.pone.0117977
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of TLR2 and TLR4 in Cytokine and Nitric Oxide Production in Visceral Leishmaniasis Patients before and after Treatment with Anti-Leishmanial Drugs

Abstract: Toll-like receptors (TLRs) have significant involvement in Leishmania infection, although little is known about the relationship between these receptors, cytokines and nitric oxide (NO) in patients with visceral leishmaniasis (VL) before or after treatment with anti-leishmanial drugs. The goal of this study was to evaluate the expression of TLR2 and TLR4 in CD3+ and CD14+ cells and the production of TNF-α, IFN-γ, IL-17, IL-10, TGF-β and NO in peripheral blood mononuclear cells (PBMCs) from VL patients pre- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 85 publications
(95 reference statements)
1
20
0
1
Order By: Relevance
“…Although TLR‐2 is deemed to alter production of NO, our data did not support a correlation with changes in expression of iNOS, in agreement with observations made in TLR‐2‐deficient mice . Of note, TNF‐α has also been previously suggested to modulate induction of iNOS, while IL‐10 was reported to have inhibitory effects on the production of the enzyme .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Although TLR‐2 is deemed to alter production of NO, our data did not support a correlation with changes in expression of iNOS, in agreement with observations made in TLR‐2‐deficient mice . Of note, TNF‐α has also been previously suggested to modulate induction of iNOS, while IL‐10 was reported to have inhibitory effects on the production of the enzyme .…”
Section: Discussionsupporting
confidence: 78%
“…We found that TLR‐2 expression was positively correlated with TNF‐α and IL‐10. Gatto et al observed similar results in human patients with active visceral leishmaniosis. These results indicate that TLR‐2 could be regulating TNF‐α and IL‐10 in an attempt to combat infection.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Additionally, the levels of TNF-α, IL-10, and TGF-β increased, and those of IFN-γ, IL-17, and NO decreased. Although the expression of these two receptors did not change in lymphocytes after treatment, in monocytes they were found to be lower for TNF-α and IL-10 and higher for TGF-β, IFN-γ, IL-17, and NO [101].…”
Section: Tlrs In the Outcome Of Disease 71 Leishmaniasismentioning
confidence: 71%